Downregulated NT-3 and PI3K/AKT signaling pathway mediates arsenic-induced apoptosis in hippocampal neurons in vivo and in vitro - Jia Cui; Ziqiao Guan; Xinbo Ma; Xinhua Shao; Kunyu Zhang; Man Lv; Meichen Zhang; Xiaona Liu; Yanhui Gao; Yanmei Yang (Ecotoxicology and Environmental Safety)
Arsenic is a neurotoxin associated with cognitive impairment following long-term exposure, while Neurotrophin-3 (NT-3) is essential for the survival and development of neurons. This study aims to explore the protective effects of NT-3 on arsenic-caused cognitive impairment and neuronal damage, as well as clarify the underlying mechanisms. In vivo and in vitro results indicated that sodium arsenite impaired cognitive function, reduced neuronal density, and induced apoptosis, which was accompanied by the down-regulation of NT-3 and the PI3K/AKT pathway. Overexpression of NT-3 in HT-22 cells mitigated apoptosis triggered by arsenic and partially restored PI3K/AKT pathway activity. Thus, our findings suggest that NT-3 may counteract the arsenic neurotoxicity by activating PI3K/AKT.